Epidermoid cyst of the cecum resected by single-incision laparoscopic colectomy: a case report - Tetsuro Tominaga; Takashi Nonaka; Akiko Fukuda; Masaaki Moriyama; Shosaburo Oyama; Mitsuhisa Ishii; Terumitsu Sawai; Nozomi Ueki; Takeshi Nagayasu (Surgical Case Reports)
Abstract Background Epidermoid cyst arising from the cecum is extremely rare. Single-incision laparoscopic surgery is the latest innovation in minimally invasive surgery, and shortens incisions, improves cosmesis, and reduces postoperative pain. We report here the first description of a patient with epidermoid cyst of the cecum treated by ileocecal resection by single-incision laparoscopic surgery. Case presentation A 20-year-old woman presented to our hospital with abdominal pain in the right lower quadrant. Abdominal contrast-enhanced computed tomography showed a 56 × 35-mm cystic mass in the ileocecal area. Magnetic resonance imaging revealed a 56 × 43-mm, T1-hypointense, T2-hyperintense mass attached to the cecum. Gastrointestinal tumor or duplication cyst was suspected, and ileocecal resection was performed using single-incision laparoscopic surgery. Intraoperative examination showed the tumor as a round, whitish mass arising from the cecum. Operation time was 162 min, and intraoperative blood loss was 10 ml. Macroscopic examination showed a 56 × 45-mm elastic-hard, whitish, round mass arising from the cecal wall. Microscopic examination revealed the cyst wall lined by keratinized stratified squamous epithelium. No malignant findings were identified. The final diagnosis was epidermoid cyst of the cecum. The postoperative course was uneventful and she was discharged on postoperative day 5. Conclusions A rare case of cecal epidermoid cyst is reported. Single-incision laparoscopic colectomy using an organ retractor represents a promising option for treating cecal epidermoid cyst.